2000
DOI: 10.1063/1.126760
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of nitrogen-doping effect on vacancy aggregation processes in Si

Abstract: Articles you may be interested inA density functional theory study of the atomic structure, formation energy, and vibrational properties of nitrogenvacancy-oxygen defects in silicon J. Appl. Phys. 108, 033513 (2010); 10.1063/1.3387912Effect of nitrogen-vacancy complex defects on the electronic transport of carbon nanotube

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 20 publications
(8 reference statements)
6
55
0
Order By: Relevance
“…43 Oxygen precipitation studies in N-doped Si have concluded that NV pairs function as precipitate nuclei 45 in agreement with first principles thermodynamic calculations, 40 which have verified the stability of NV defects. Remarkably, it has been shown theoretically that a N2V2 structure is the most stable form of N-V defects 40 , and it has also been suggested to act as oxygen precipitate nuclei. 39,46,47 On the other hand, N is expected to react with SiI, and the formation of a (Ni)2SiI defect has been studied theoretically.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…43 Oxygen precipitation studies in N-doped Si have concluded that NV pairs function as precipitate nuclei 45 in agreement with first principles thermodynamic calculations, 40 which have verified the stability of NV defects. Remarkably, it has been shown theoretically that a N2V2 structure is the most stable form of N-V defects 40 , and it has also been suggested to act as oxygen precipitate nuclei. 39,46,47 On the other hand, N is expected to react with SiI, and the formation of a (Ni)2SiI defect has been studied theoretically.…”
Section: Introductionsupporting
confidence: 51%
“…31,36,[38][39][40]43,44 Indeed, N pairs with a V to form N-V complexes as has been determined through positron annihilation spectroscopy studies in N implanted Si. 43 Oxygen precipitation studies in N-doped Si have concluded that NV pairs function as precipitate nuclei 45 in agreement with first principles thermodynamic calculations, 40 which have verified the stability of NV defects. Remarkably, it has been shown theoretically that a N2V2 structure is the most stable form of N-V defects 40 , and it has also been suggested to act as oxygen precipitate nuclei.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Schultz and Nelson found an energy barrier of 0.4 eV for the diffusion of the split-interstitial nitrogen [23]. Our study of bond-centered nitrogen found a 0.44 eV migration barrier through a simple path, but a calculation of the temperature-dependent prefactor gave that the diffusion constant is best fit by an Arrhenius expression of D N 1:7e ÿ0:56=kT cm 2 =s (6) in the temperature range from 800 -1600 K. At low temperatures, an exponent of 0.50 eV better describes the diffusion constant. With these values, the N i will diffuse at least 5 orders of magnitude faster than N 2 pairs.…”
Section: Prl 95 025901 (2005) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 88%
“…N 2 V 2 or N 2 V 2 ! N 2 V 2 [5,6]. The N 2 V 2 complex has been shown to attract oxygen into stable complexes, indicating the possibility of further oxygen precipitate nucleation based on the N 2 pair.…”
mentioning
confidence: 99%